U.S. Chinese relations in a Global Perspective - Fawcett, Alicia; Maslowski, Nicolas, 1972-; Druláková, Radka, 1973-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2014)
Title: Diplomacy with Chinese Characteristics: The Cultural Aspect of Chinese Foreign Policy in the Example of Sino-American Relations Ambiguity in answers, lack of communication or justification of actions have resulted in a negative depiction of Sino-American relations. I would like to prove the cultural significance as a major factor in influencing Chinese foreign policy regarding the example of Sino-American relations. By applying elements of constructivism, one is able to understand the cultural perspective of Chinese foreign policy in the example of Sino-American relations. Furthermore, this is proven through philosophical application of game theory stratagem.
Vedoucí práce: Nicolas Maslowski
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses